Digital Microlearning and Self-Regulated Learning: Exploring Learners’ Experiences toward Sustainable Learning - Arinal Haq Fauziah; Ishlakhatus Sa’idah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Technological advances in digital learning have led to the transformation of education through flexible microlearning, but its effectiveness is greatly influenced by the self-regulated learning (SRL) capacity of students in managing their learning processes. This study aims to examine participants' experiences of utilising digital microlearning through the Ruang Karya platform, as well as the role of SRL in promoting continuous learning. The study used a qualitative approach with a phenomenological method to understand the meaning of the learning experience directly experienced by the participants. Data were collected through in-depth interviews until saturation was reached. The results of the study show that digital microlearning provides easy access, time flexibility, and concise, focused material presentation, thus increasing learning efficiency. However, the effectiveness of this is greatly influenced by SRL skills such as time management, goal setting, learning strategies, and self-monitoring and evaluation. Participants with good SRL skills tend to have a more optimal and meaningful learning experience. Integrating microlearning digital and SRL also promotes independent learning, increases intrinsic motivation, and strengthens preparedness to face academic and future challenges. Therefore, strengthening SRL is crucial in optimising microlearning digital as a sustainable learning strategy in the digital era.